Considerations in light truck suspension design - Hugo Mathias, Mauro [UNESP]; Eduardo Michelini, José; La Selva, Marli; Henrique Baptista, Luiz; Augusto Pagan, José (SAE International, 2000)
The present work aims at to approach considerations of trucks suspension design. The proposal of the work consists of discussing the aspects related to the acting of the suspension and of factors that interact with the system through representative models of the dynamic behaviour of the vehicle ride when operating in total load and/or empty conditions. The importance of this work is to revise some procedures of suspension study in the sense of adapting them to the Brazilian reality, tends in view the importance of the design characterisation and adaptation to the typical roads of Brazil. Copyright © 2000 Society of Automotive Engineers, Inc.
Keywords: Dynamic behaviours; Light trucks; Suspension design; Total load; Vehicle ride; Automobiles; Design; Suspensions (components)